2018
DOI: 10.1177/0192513x18800787
|View full text |Cite
|
Sign up to set email alerts
|

Family Meal Practices and Well-Being in Hong Kong: The Mediating Effect of Family Communication

Abstract: The literature has provided substantial evidence for the positive associations between family meals and well-being. The underlying mechanism of this relationship has not been explicitly examined. The Happy Family Kitchen II project was a cluster randomized controlled trial of a community-based family intervention. Using data from this project, this article examined the direct and indirect associations among family meal practices, family communication time and quality, and well-being in Hong Kong. A total of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
2
9
0
3
Order By: Relevance
“…Our findings of mediating effects of communication sufficiency and quality reflected the contributing role of family communication to family well-being in Olson's Circumplex Model of Family Systems (Olson, 2000), McMaster Model of Family Functioning (Epstein et al, 1978), and our community-based intervention studies (Ho et al, 2018;. The negative association between PSU and family communication was consistent with previous findings that Internet addiction was associated with lower levels of quantity and quality of parent-adolescent communication (Lei & Wu, 2007;Liu, Lin, Zhou, & Zhang, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings of mediating effects of communication sufficiency and quality reflected the contributing role of family communication to family well-being in Olson's Circumplex Model of Family Systems (Olson, 2000), McMaster Model of Family Functioning (Epstein et al, 1978), and our community-based intervention studies (Ho et al, 2018;. The negative association between PSU and family communication was consistent with previous findings that Internet addiction was associated with lower levels of quantity and quality of parent-adolescent communication (Lei & Wu, 2007;Liu, Lin, Zhou, & Zhang, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…One explanation might be that family communication facilitates the development of emotional connections within families and enables family members to express and share attitudes, values, and beliefs and to be flexible in changing family's leadership, roles, and rules (Epstein, Bishop, & Levin, 1978;Olson, 2000). Our communitybased interventions provided experimental evidence that family well-being could be promoted through perceived sufficient time and high quality of family communication (Ho et al, 2018;.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, it has been reported that poor relationships with parents in childhood and adolescence are associated with greater odds of health and behavioral problems later in life [ 4 , 12 ]. On the other hand, frequent and open communication between parents and children can increase mutual understanding of each other thereby enhancing family relationship [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…선 행연구를 살펴보면 가족식사의 의례성은 가족의 친밀감과 유대 감 (Compan et al, 2002), 가족생활만족도 (Kim & Park, 2013;Kim & Um, 2014), 가족응집성과 가족적응성 (Bae, 2016;Bae & Park, 2017;Choi, 2018 (Berge, Draxten et al, 2018;Trofholz et al, 2017). 또한 가족식사를 위한 역할분담이 원활하게 이루어 질 때 가족생활만족도 (Fulkerson et al, 2011;Ho et al,…”
unclassified